THE INFLUENCE OF CASH FLOW COMPONENTS AND ACCOUNTING INCOME ON STOCK RETURN (Study on LQ45 index Companies on the Indonesia Stock Exchange) - Givari, Muhammad Arbiant (Jurnal KIAFE, 2021)
This study aims to determine the effect of operating cash flow, investing cash flow, financing cash flow and accounting income on stock returns. The method used is a quantitative method. The data in this study were obtained from the company's quarterly reports. The sample of this study was selected using a purposive sampling method on companies that are included in the LQ45 index listed on the Indonesia Stock Exchange in a row in 2018-2019. The sample used in this study were 30 companies from 45 companies. The method of analysis of this research is using multiple linear regression analysis. The results of this study indicate that operating cash flow affects stock returns, investing cash flow does not affect stock returns, financing cash flow does not affect stock returns, while accounting income affect stock returns. Keywords: Cash flow components, operating cash flow, investing cash flow, financing cash flow, accounting income, return stock. Penelitian ini bertujuan untuk mengetahui pengaruh Arus Kas Operasi, Arus Kas Investasi, Arus Kas Pendanaan dan Laba Akuntansi terhadap return saham. Metode yang digunakan adalah metode kuantitatif. Data pada penelitian ini diperoleh dari laporan kuartal perusahaan. Sampel penelitian ini diseleksi dengan menggunakan metode purposive sampling pada perusahaan yang termasuk indeks LQ45 terdaftar di Bursa Efek Indonesia berturut-turut pada tahun 2018-2019. Sampel yang digunakan dalam penelitian ini sebanyak 30 perusahaan dari 45 perusahaan. Metode analisis dari penelitian ini menggunakan analisis regresi linear berganda. Hasil dari penelitian ini menunjukkan bahwa Arus Kas Operasi berpengaruh terhadap return saham, Arus Kas Investasi tidak mempengaruhi return saham, Arus Kas Pendanaan tidak mempengaruhi return saham, sedangkan laba akuntansi dapat mempengaruhi return saham. Kata kunci: Komponen aru